Taxonomic identity of Impatiens cathcartii Hook.f. & I. serratifolia Hook.f. with notes on typification of both names - Gogoi, Rajib; Sherpa, Norbu (Biodiversity: Research and Conservation, 2020)
Impatiens cathcartii Hook.f. is recollected almost after a century, its taxonomic identity, description from fresh collection, coloured illustrations are made along with notes on typification of the name. Taxonomic identity of I. serratifolia Hook.f. along with its delimitation from closely related species is discussed, coloured illustrations with comparison of flowers with the closest species and notes on the typification of the name are also discussed.